The Impact of Achmea on Investor-State Arbitration under Intra-EU BITs: A Treaty Law Perspective (Polish Yearbook of International Law, 2021)
This article examines the consequences of the Court of Justice of the European Union’s (CJEU) ruling in Achmea concerning Investor-State Arbitration (ISA) under intraEU Bilateral Investment Treaties (BITs) from a treaty law perspective. It begins by briefly setting out the arguments of Advocate General Wathelet and the CJEU supporting their different positions on whether intra-EU BITs ISA clauses are compatible with EU law. The article then proceeds to analyse Achmea’s implications for intra-EU BIT ISA. It concludes that, as a result of the CJEU’s ruling, arbitral tribunals are deprived of their jurisdiction to entertain investors’ claims brought under intra-EU BIT ISA clauses. Finally, the article argues that Achmea’s applicability to cases brought under intra-EU BIT ISA clauses is limited, using the application of EU law as a relevant qualification. In order for an arbitral tribunal to be deprived of its jurisdictional competence as a result of Achmea, it must be entitled to interpret and apply EU law directly or indirectly in determining its jurisdiction.